African American Dementia Caregivers' Perspectives on and Appraisal of Stress Associated with the Caregiving Role: A Qualitative Study. (20th December 2022) - Block, Laura M; Cotton, Quinton; Seyyedmirza, Paria; Chang, Juliet; Gilmore‐Bykovskyi, Andrea L
Abstract: Background: African Americans are disproportionately impacted by Alzheimer's disease and related dementias (ADRD), with family members providing the majority of support and care. Dementia caregivers often face high levels of stress and burden which contribute to poor physical and psychological health outcomes. African American dementia caregivers often face greater risk for stress and burden with discrepant evidence on whether this leads to worse outcomes compared to counterparts. Yet African American dementia caregivers remain under‐included in research designed to understand and ameliorate the stress and burden of caregiving. Our study aimed to understand African American dementia caregivers' perspectives and appraisal of stressors surrounding caregiving and stressful events, such as hospitalization of the person with ADRD. Methods: We harnessed qualitative interview data from the Stakeholders Understanding of Prevention Protection and Opportunities to Reduce HospiTalizations (SUPPORT) Study, a multi‐site study designed to determine family caregiver perspectives surrounding hospitalizations for people with ADRD residing in highly disadvantaged neighborhoods. Data from 30 dementia caregivers who self‐identified as African American were analyzed using thematic analysis. Results: All participants described the presence of stressors and stressful events related to their life broadly and to dementia caregiving more specifically. However, there was great variation in the described degree of stressors in caregiver's daily life. Caregivers experiencing a greater number, more recent, and more acute stressors described greater burden in their daily life. Long‐standing stressors, such as family conflict and financial hardship, sometimes 'resurfaced' with the proximity and role changes brought on by caregiving. Other individual and situational factors, such as one's own health or status as a 'sandwich caregiver, ' or the habits and preferences of the person with ADRD, could serve as contributors to overall stress. Few caregivers related stressors to long‐term outcomes, though some described strategies to seek formal mental health counseling. Conclusions: African American dementia caregivers described a variety of acute and ongoing stressors that related not only to caregiving for the person with ADRD but also the caregiver's personal health and their broader familial and neighborhood context, signaling the need for adaptive caregiver support interventions capable of addressing intervention targets across various stressors.